PERAN UNIT COUNTER TRAFFICKING INTERNATIONAL ORGANIZATION FOR MIGRATION (IOM) DALAM MENANGANI ANCAMAN KEAMANAN NON-TRADISIONAL (PERDAGANGAN TKI ILEGAL) DI PROVINSI NTB - Muhammad Jaya Anggara Putra; Obsatar Sinaga; Arry Bainus (Dinamika Global : Jurnal Ilmu Hubungan Internasional, 2018)
The problem of human trafficking under the guise of illegal TKI trade (Human Trafficking) is still a crime that can threaten human security throughout the world including in Indonesia and more particularly in four districts in West Nusa Tenggara, West Lombok, Central Lombok Regency, East Lombok Regency, and North Lombok Regency. IOM Indonesia's Counter Trafficking Unit is one of the international organizations that have the task of dealing with human trafficking issues. With the sense of need to play an active role in overcoming the problem of illegal TKI trade in NTB, therefore Counter Trafficking Unit cooperates with NTB government to jointly seek various strategies to create human security in the form of illegal kindergarten trade in four districts namely West Lombok regency, Central Lombok, East Lombok Regency, and North Lombok Regency of West Nusa Tenggara Province. The methodology used by researchers in this research is qualitative method with descriptive technique. This method according to the researchers will be able to describe and explore problems that occur systematically, valid, factual and accurate. Furthermore, the main purpose of this research is to see how the role of Counter Trafficking Unit in assisting NTB Government to overcome the illegal trade of migrant workers by Traffickers (Calo/ PJTKI) in NTB. The conclusion of this research is IOM Counter Trafficking Unit has a role set in handling the problem of illegal TKI trade in NTB, ie as role expection, strengthening of role conception, establishing partnership with NTB government from 2001 -2018.